2018
DOI: 10.1186/s13071-018-2797-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an injectable toltrazuril-gleptoferron (Forceris®) and an oral toltrazuril (Baycox®) + injectable iron dextran for the control of experimentally induced piglet cystoisosporosis

Abstract: BackgroundCystoisospora suis causes diarrhoeal disease and reduced weight gain in suckling piglets, and a toltrazuril-based oral suspension is available for treatment. Recently a combinatorial product with toltrazuril plus iron has been developed for parenteral application. In this study we compared the efficacy of the injectable product with the oral suspension against experimentally induced piglet cystoisosporosis.MethodsIn a randomised controlled study, three groups of piglets (n = 10–13) were treated eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“… Rypula et al (2012) and Mundt et al (2003b) demonstrated the positive effect of toltrazuril treatment on body weight gains in infected piglets. In agreement with a previous report on Forceris® treatment of experimentally infected piglets ( Joachim et al, 2018b ), we confirmed significantly improved body weight gains in naturally coccidiosis exposed piglets.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… Rypula et al (2012) and Mundt et al (2003b) demonstrated the positive effect of toltrazuril treatment on body weight gains in infected piglets. In agreement with a previous report on Forceris® treatment of experimentally infected piglets ( Joachim et al, 2018b ), we confirmed significantly improved body weight gains in naturally coccidiosis exposed piglets.…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of Forceris ® was confirmed in comparison with an established reference product (oral toltrazuril suspension; Baycox ® 5% - Bayer Animal Health) by Joachim et al (2018b) . Results were obtained in an experimental infection model only, described by Mundt et al (2006) , but field data needed to be generated.…”
Section: Introductionmentioning
confidence: 80%
“…Oocyst detection can be accomplished by detection in faecal smears with autofluorescence or, with relatively lower sensitivity, after carbol-fuchsin staining, and can be judged semi-quantitatively. Determination of OpGs by adapted McMaster counting is usually applied under experimental conditions and for specific applications, such as an in vivo faecal oocyst reduction test to evaluate treatment efficacy [ 49 ]; however, this requires precise knowledge about the extent and intensity of infection and the course of infection on the farm in question.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired intestinal homeostasis and slow regeneration of the intestinal epithelium in infected piglets lead to significant reductions in body weight gain, most likely due to reduced nutrient absorption (Mundt et al, 2003(Mundt et al, , 2006Joachim and Mundt, 2011). The disease is effectively controlled by oral or parenteral administration of a single dose of the triazinone toltrazuril during the developmental phase of C. suis in the host (Mundt et al, 2006;Joachim et al, 2018cJoachim et al, , 2019. The exact mode of action of toltrazuril is not known but it has been suggested that toltrazuril interferes with nuclear division and mitochondrial activity in coccidian parasites (Harder and Haberkorn, 1989).…”
Section: Introductionmentioning
confidence: 99%